How Does Rasch Model Reveal Dishonesty between Coastal Students and Easy Grammar Test? - Satria Agust (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
Academic dishonesty can occur with the supports of the technology devices and it also can be prevented with the help of the technology with its applications like Rasch Model. It can give detail information of the analyzed data and can trace the academic dishonesty like cheating. The aims of this research are to (1) analyze the grammar test items whether they are difficult items or easy ones using Rasch Model, (2) know the percentage of those who are assumed to do cheating based upon their origins and sex, and (3) expose their patterns in working on the grammar test in the form of multiple choice through the Rasch Model analysis. The researcher hypothesized that the academic dishonesty i.e. cheating was undergone by students who are from rural and urban areas of Riau Archipelago Province. The results of this research were: (1) through the students’ responses analyzed by Rasch Model, the grammar test was for medium ability, (2) The Rasch Model revealed that the percentage came to the number 5.71% or 4 of 70 students who were identified to cheat while working on the grammar test. They were two female students from rural area and the other two male students from urban area, and (3) The Rasch Model revealed that their responses did not represent their ability. The Rasch Model has helped the researcher to exposes the cheating deeds on exams. The practitioners just need methods, approaches, strategies, techniques, and media to prevent them in the future Keywords: Rasch Model, Wright Maps, Grammar Test.